The results of local excision with or without postoperative adjuvant chemoradiotherapy for early rectal cancer among patients choosing to avoid radical surgery. (February 2017) - Balyasnikova, S.; Read, J.; Tait, D.; Wotherspoon, A.; Swift, I.; Cunningham, D.; Tekkis, P.; Brown, G.
Abstract: Aim: The study aimed to establish the oncological outcome of patients who opted for close surveillance with or without adjuvant chemoradiotherapy rather than radical surgery after local excision (LE) of early rectal cancer. Method: The Royal Marsden Hospital Rectal Cancer database was used to identify rectal cancer patients treated by primary LE from 2006 to 2015. All patients were entered in an intensive surveillance programme. Results: Twenty‐eight of 34 analysed patients had a high or very high risk of residual disease predicted by adverse histopathological features for which the recommendation had been radical surgery. Eighteen (52%) of the 34 had received radiotherapy following LE. Three‐year disease‐free survival for the 34 patients was 85% (95% CI 78.8%–91.2%) and overall survival was 100%. Twenty‐two of 24 patients with a low tumour which would have required total rectal excision have so far avoided radical surgery and remain disease free at a median follow‐up of 3.2 years. Conclusion: The findings suggest that with modern MRI and clinical surveillance radical surgery can be avoided in patients following initial LE of a histopathologically defined high risk early rectal cancer. These findings are comparable with those obtained after major radical resection and warrant further prospective investigation as a treatment arm in larger prospective trials.